HR Perspective To Optimized Of Bumdes Financial Management - Editya Nurdiana (CV. AFDIFAL MAJU BERKAH, 2024)
The goal of this study is to examine HRM practices in the context of digital financial management for BUMDes. In order to facilitate labor, it is imperative that the need for digitization be met. BUMDes business owners may find it simpler to access structured data and information with digitalized financial reports. This study strategy combines a qualitative methodology with a literature review methodology. The references to the Village Government Law, pertinent scholarly publications, and books on village finance management are used as the data sources. use document analysis to analyze data. The study's conclusions are as follows: BUMdes managers need to be competent in internationalizing archive management; The creation of financial SOPs requires the integration of BUMDes managers. These managers gather accurate digital accounting reports and administrative records, enabling them to offer management accountability for the government's capital participation fund utilization.